(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article explores the life and creative work of Islom Shoir Nazar ogli, a representative of the Narpay epic school. It analyzes the plot of the epic "Orzigul", performed by him, and its significance in the artistic legacy of the bakhshi tradition.